Surface Design and Strength Analysis of Porous Linear Diaphragm - Kangkang Ding; Yinxin Yu; Yingxian Zhang (Jixie chuandong, 2021)
Titanium alloy curvature diaphragm is the main diaphragm type of existing flexible diaphragm couplings. Due to its thin thickness， its difficult curved surface processing and requires high precision， a porous linear diaphragm is improved in order to reduce the processing difficulty and ensure the diaphragm has better tolerance and load capacity. The finite element method is used to analyze its axial stiffness， stress and durability under torque， axial deviation， angular misalignment deviation， rotating speed and composite working conditions， and compared it with the single-curvature diaphragm with the same diameter. The research shows that the axial stiffness of the porous linear diaphragm is smaller than that of the single-curvature diaphragm with the same diameter， which also shows nonlinear variation and is proportional to the thickness of the diaphragm. Under axial deviation and angular misalignment deviation， the stress is lower than that of the single-curvature diaphragm， thus having better tolerance capability. Under the same load torque， the stress is larger than that of the single-curvature diaphragm， but it meets the requirements of strength and durability， and the stress distribution of the diaphragm is more uniform. Therefore， the porous linear diaphragm has higher tolerance performance and is suitable for engineering environments with high rotating speed， low load and large axial and angular misalignment deviation.